Bioaccumulation of heavy metals in Liza saliens from the Esmoriz-Paramos coastal lagoon, Portugal - Fernandes, Conceição (2011)
http://apps.isiknowledge.com/full_record.do?product=UA&search_mode=GeneralSearch&qid=3&SID=T2n6@BOd@6lKkDK3EB3&page=1&doc=1&colname=WOS